Initiation and adherence to isoniazid preventive therapy in children under 5 years of age in Manhiça, Southern Mozambique. (30th January 2023) - Montoya i de Manuel-Rimbau, Agnès; Nguenha, Dinis; Mambuque, Edson; Ehrlich, Joanna; Munguambe, Shilzia; Saavedra, Belén; Matsena, Teodimiro; Chiconela, Hélio; Casellas, Aina; López-Varela, Elisa; Acacio, Sozinho; Garcia-Basteiro, Alberto L
Abstract: The WHO recommends preventive treatment for all pediatric contacts of a confirmed TB case, but coverage remains low in many high TB burden countries. We aimed to assess the coverage and adherence of the isoniazid preventive therapy (IPT) program among children under 5 years of age with household exposure to an adult pulmonary TB case in a rural district of Southern Mozambique. The estimated IPT coverage was 11.7%. A longer distance to the health center and lower age of the children hindered IPT initiation. Among patients who started IPT, 12/18 (69.9%) were adherent to the 6-month treatment.